The Effect of Happy Gymnastics Program on 3-6Years Old Children’s Balance in Haian Foreign Language Kindergarten - Suying, Wang; Promthep, Kreeta; Duangkam, Jakrin; Sukityarn , Pongsatorn; Khantiyu , Yodkhwan (Journal of Roi Kaensarn Academi, 2024)
Balance ability is one of the most basic motor skills, representing the basic physical quality of human beings, it plays a very important role in our future study, work, and life. The content of happy gymnastics includes strength, speed, flexibility, sensitivity, endurance and other aspects of training, which is more in line with children’s psychological and physical development. The objectives of this research are: compare the effect of balance training on balance in children aged 3-6 years old between the experimental group using the Happy Gymnastics Program and the control group using the Traditional Gymnastics Program. Research sample: 60 students from primary class (3-4 years old), secondary class (4-5 years old) and senior class (5-6 years old) of Haian Foreign Language Kindergarten were selected as the experimental group and the control group respectively. The experimental class carried out the 12-week happy gymnastics intervention experiment. Before and after the intervention, the United States foot scan balance tester instrument system was used to conduct eye-opening test of both feet, closed-eye test of both feet, eye-opening test of one foot and closed-eye test of one foot. Results: 1. After the experimental intervention of happy gymnastics, the static balance ability of children in the experimental class with opening or closed eyes respectively reached the most significant level (p<0.01), a normal significant level (p<0.05) and a small significant level (p<0.1), while there was no statistical significance in the control class (p>0.1). 2. After the experimental intervention of happy gymnastics, the children’s static eye opening and closed eyes balance ability of one foot in the experimental class was more significantly improved than that of both feet, while there was no statistical significance in the control class (p>0.1). Conclude the basic movements of happy gymnastics: crawling, running, jumping tumbling exercises, balance exercises, and physical exercises have obvious effects on children’s balance ability.